Copper based mixed oxide catalysts (CuMnCe, CuMnCo and CuCeZr) for the oxidation of CO at low temperature. (December 2017) - Dey, Subhashish; Mohan, Devendra; Dhal, Ganesh Chandra; Prasad, Ram
Graphical abstract: Abstract: The effect of surface enrichment in mixed metal oxides of CuMnCe, CuMnCo, and CuCeZr catalysts is highly effective for CO oxidation. The present work describes the preparation of CuMnCe, CuMnCo and CuCeZr catalysts and the characterization techniques applied to gain information about the catalyst structure and activity. Among the catalysts, CuMnCe and CuMnCo were prepared by the co-precipitation method and another catalyst CuCeZr was prepared by the reactive grinding method. In the variety of mixed metal oxide catalysts, CuMnCe was considered to be the most effective for high activity. The addition of ceria in CuMnOx catalyst has also improved the activity and stability due to increasing the meso/macropore volume and surface area after aging treatment. A novel route of reactive calcination (RC) of the precursor was the synthesis of highly active catalyst. The amazing activity of the novel catalysts over the conventional ones (obtained by calcination of the precursors in stagnant air and flowing air) in CO oxidation was associated with the unusual morphology as evidenced by XRD, SEM-EDX, XPS, BET and FTIR characterization. The catalysts obtained by RC of various precursors showed the highest activity for CO oxidation in the following order: CuMnCe > CuCeZr > CuMnCo and the traditional route of calcination also followed the same activity order. Further, the activity order of the catalysts obtained by various calcination conditions was as follows: RC > flowing-air > stagnant-air.